2002
DOI: 10.1136/bjo.86.8.902
|View full text |Cite
|
Sign up to set email alerts
|

Epiretinal pathology of vitreomacular traction syndrome

Abstract: Aims: To investigate the ultrastructure of the vitreoretinal interface in patients with vitreomacular traction syndrome. Methods: 14 patients with vitreomacular traction syndrome underwent standard pars plana vitrectomy. After induction of posterior vitreous detachment, epiretinal tissue and the inner limiting membrane (ILM) of the retina were removed, and processed for transmission electron microscopy. Results: Ultrastructural analysis revealed two basic patterns of vitreoretinal pathology in eyes with vitreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
72
2
20

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 151 publications
(94 citation statements)
references
References 34 publications
0
72
2
20
Order By: Relevance
“…[15][16][17][18] This is in contrast to previous histologic studies of vitreomacular traction that found predominately myofibroblasts, fibrocytes, fibrous astrocytes, and an absence of RPE cells. [11][12][13][14] However the previous studies examined specimens removed from the surface of the retina at the site of vitreoretinal attachment and did not concentrate on the vitreous cone above the retina as we did.The ERM and the ILM specimens removed showed native collagen sandwiched between the ILM and RPE cells. A PVD appears to form by a splitting within the vitreous cortex, leaving remnants of vitreous on the foveal surface.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…[15][16][17][18] This is in contrast to previous histologic studies of vitreomacular traction that found predominately myofibroblasts, fibrocytes, fibrous astrocytes, and an absence of RPE cells. [11][12][13][14] However the previous studies examined specimens removed from the surface of the retina at the site of vitreoretinal attachment and did not concentrate on the vitreous cone above the retina as we did.The ERM and the ILM specimens removed showed native collagen sandwiched between the ILM and RPE cells. A PVD appears to form by a splitting within the vitreous cortex, leaving remnants of vitreous on the foveal surface.…”
mentioning
confidence: 93%
“…1,2 Our understanding of VMT has been enhanced by the development of optical coherence tomography (OCT), a noninvasive method of imaging intraocular tissues. [3][4][5][6][7][8][9][10][11] Inquiries to Richard F. Spaide, Vitreous, Retina, Macula Consultants of New York, 460 Park Avenue, 5th Floor, New York, NY 10022; rickspaide@yahoo.com. Idiopathic epiretinal membrane (ERM) proliferation is another vitreoretinal interface abnormality that is often considered to be distinct from VMT.…”
mentioning
confidence: 99%
“…11 Clinically, only the latter type can be identified as a clearly visible epimacular membrane. From the clinical and histopathological point of view, one might expect the present case to be analogous to a type (b) membrane configuration.…”
Section: Discussionmentioning
confidence: 99%
“…9 It is interesting to note that myofibroblasts, astrocytes, and fibrocytes, predominate also in vitreomacular traction syndrome, 10,11 whereas retinal pigment epithelial cells are commonly found in ERM. 12,13 Radiating retinal folds in eyes with PVA may represent vitreous traction concentrated in the center of the fold (Figure 3).…”
Section: Discussionmentioning
confidence: 99%